Indomethacin-induced morphologic changes in the rat urinary bladder epithelium - ERCAN, FERİHA (My University, 2003)
OBJECTIVES: To evaluate the morphologic changes in rat urothelium induced by indomethacin. Nonsteroidal anti-inflammatory drug-induced cystitis is a poorly recognized and under-reported condition. In addition to tiaprofenic acid, indomethacin has been reported to be associated with this condition. METHODS: Three groups were established: a control group (n = 10), a high-dose group (n = 10), treated with one intraperitoneal injection of indomethacin 20 mg/kg, and a therapeutic dose group (n = 10) in which oral indomethacin was administered 3.25 mg/kg body weight daily for 3 weeks. The animals were then killed and the bladders removed for light and electron microscopic studies. RESULTS: The light microscopic findings showed some focal epithelial degeneration that was more prominent in the high-dose group. When compared with the control group, both indomethacin groups revealed statistically increased numbers of mast cells in the mucosa (P <0.0001) and penetration of lanthanum nitrate through intercellular areas of the epithelium. Furthermore, the difference in mast cell counts between the high and therapeutic dose groups was also statistically significant (P <0.0001). CONCLUSIONS: Indomethacin resulted in histopathologic findings typical of interstitial cystitis, such as leaky bladder epithelium and mucosal mastocytosis. The true incidence of nonsteroidal anti-inflammatory drug-induced cystitis in humans must be clarified by prospective clinical trials.
Keywords: Animals; Rats; Cell Count; Urinary Bladder Neoplasms; Microscopy, Electron, Scanning; Dose-Response Relationship, Drug; Rats, Sprague-Dawley; Anti-Inflammatory Agents, Non-Steroidal; Injections, Intraperitoneal; Cystitis, Interstitial; Urinary Bladder; Indomethacin; Mast Cells; Urothelium; Mastocytosis